Mortality and Cancer Incidence in Carriers of Balanced Robertsonian Translocations: A National Cohort Study. Issue 3 (7th December 2019) - Schoemaker, Minouk J; Jones, Michael E; Higgins, Craig D; Wright, Alan F; ,; Swerdlow, Anthony J
Abstract: A balanced robertsonian translocation (rob) results from fusion of 2 acrocentric chromosomes. Carriers are phenotypically normal and are often diagnosed because of recurrent miscarriages, infertility, or aneuploid offspring. Mortality and site-specific cancer risks in carriers have not been prospectively investigated. We followed 1, 987 carriers diagnosed in Great Britain for deaths and cancer risk, over an average of 24.1 years. Standardized mortality and incidence ratios were calculated comparing the number of observed events against population rates. Overall mortality was higher for carriers diagnosed before age 15 years (standardized mortality ratio (SMR) = 2.00, 95% confidence interval (CI): 1.09, 3.35), similar for those diagnosed aged 15–44 years (SMR = 1.06, 95% CI: 0.86–1.28), and lower for those diagnosed aged 45–84 years (SMR = 0.81, 95% CI: 0.68, 0.95). Cancer incidence was higher for non-Hodgkin lymphoma (standardized incidence ratio (SIR) = 1.90, 95% CI: 1.01, 3.24) and childhood leukemia (SIR = 14.5, 95% CI: 1.75, 52.2), the latter particularly in rob(15;21) carriers (SIR = 447.8, 95% CI: 11.3, 2, 495). Rob(13;14) carriers had a higher breast cancer risk (SIR = 1.58, 95% CI: 1.12, 2.15). Mortality risks relative to the population in diagnosed carriers depend on age at cytogenetic diagnosis, possibly reflecting age-specific cytogenetic referral reasons. Carriers might be at greater risk of childhood leukemia and non-Hodgkin lymphoma and those diagnosed with rob(13;14) of breast cancer.